Grade III Pseudoaneurysm of Right Common Carotid Artery Following Blunt Trauma - A Case Report (Bangladesh Journal of Radiology and Imaging, 2026)
Post traumatic pseudoaneurysm of common carotid artery is uncommon, but can lead to life threatening complications. Early diagnosis of this rare entity is very much important for treatment planning and good prognosis. Multi Detector Computed Tomography (MDCT) plays a very important role in this regard. A 42 years old gentleman presented with pulsatile neck swelling one and half months after road traffic accident. Contrast enhanced MDCT revealed pseudoaneurysm of right common carotid artery (CCA).The patient was advised for endovascular treatment. Our report also suggests that, any patient with history of blunt or penetrating trauma in carotid region should go through a standard investigative work-up for early diagnosis of any carotid arterial injury.BJRI, 2024; VOL. 32(2): 142-144